2021
DOI: 10.3390/plants10081532
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Effect on the Grain Yield of Three Drought-Tolerant Maize Varieties under Varying Growth Conditions

Abstract: A rise in global temperature will reduce maize yield, particularly in Africa, where maize is a staple food. Therefore, improving maize yield under heat stress will promote food security in the region. The objective of this study was to assess the influence of heat stress on the grain yield of drought-tolerant maize varieties under varied growth conditions. The experimental design used was a 2 × 3 × 3 × 2 factorial fitted into a completely randomized design with four replications. The factors were heat stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
(86 reference statements)
2
22
0
Order By: Relevance
“…Since grain yield determines the economic value of maize varieties, the treatment interactions' progenies were clustered in this study based on yield-related attributes. The findings in this study that GWt and CWt were the most informative attributes agreed with previous reports on maize studies [3,33,34].…”
Section: Interaction Of Parental Heat Stress Maize Variety and Soil Amendment On The Progenies' Growth And Yield Attributessupporting
confidence: 93%
See 4 more Smart Citations
“…Since grain yield determines the economic value of maize varieties, the treatment interactions' progenies were clustered in this study based on yield-related attributes. The findings in this study that GWt and CWt were the most informative attributes agreed with previous reports on maize studies [3,33,34].…”
Section: Interaction Of Parental Heat Stress Maize Variety and Soil Amendment On The Progenies' Growth And Yield Attributessupporting
confidence: 93%
“…This finding highlights the importance of including heat stress tolerance in maize cultivar development [20]. It has been demonstrated that the response of maize plants to a single stressor differs from the synergistic effect of multiple stressors [3,4]. However, more research is needed to determine how these stressors affect maize progeny.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations